Penerapan Internet Banking Dan Mobile Banking Pada Kinerja Keuangan Bank Umum Konvensional Di Indonesia - Erra Fazira; Hapsari, Dian Indriana (LPPM Universitas Pelita Bangsa, 2023)
This study aims to determine the effect of internet banking and mobile banking on the financial performance of conventional commercial banks on the IDX in 2018-2021. This research uses descriptive verification method. The use of multiple linear regression in data processing. Data was collected through non-participant observation methods by taking data in the form of financial reports on the IDX. Patially, only mobile banking has a significant effect on banking financial performance. Simultaneously, the two independent variables have a significant influence on banking financial performance